ChemInform Abstract: An Antibacterial ortho‐Quinone Diterpenoid and Its Derivatives from Caryopteris mongolica. Issue 39 (September 2015) - Saruul, Erdenebileg; Murata, Toshihiro; Selenge, Erdenechimeg; Sasaki, Kenroh; Yoshizaki, Fumihiko; Batkhuu, Javzan
Abstract The new antibacterial ortho‐quinone diterpenoid caryopteron A (I) and its derivatives caryopteron B (II), C (III), and D (IV) are isolated from Caryopteris mongolica together with three known compounds.